Transfer of Inuit qaujimajatuqangit in modern Inuit society - Laugrand, Frédéric; Oosten, Jarich (Études/Inuit/Studies, 2009)
This paper explores the nature and transfer of Inuit knowledge. Using our experiences in setting up workshops with elders and youths in the past 10 years, we argue that the notion that Inuit qaujimajatuqangit can be viewed as a corpus of knowledge that can be integrated into academic programs is necessarily flawed. We suggest that more room should be given to Inuit elders and their knowledge by adapting the school system to Inuit perspectives rather than the reverse. Cet article examine la nature des savoirs inuit et leur transmission. À partir de notre expérience dans l’organisation d’ateliers avec des aînés et des jeunes au cours des 10 dernières années, nous avançons l’idée que la présentation de l’Inuit qaujimajatuqangit comme un corpus de savoirs qui pourrait être intégré dans les programmes d’études est une entreprise nécessairement biaisée. Nous suggérons qu’il faudrait accorder plus de place aux aînés inuit et à leur savoir en adaptant le système scolaire aux perspectives inuit et non l’inverse.